IMPROVEMENT OF LEARNING INTEREST THROUGH POWERPOINT ON THE NATURAL IMPACT MATERIALS OF CLASS IV STATE SD PASI PINANG - Yulia Maulida (Teunuleh Publisher, 2020)
The purpose of this study was to determine the increase in interest in learning by using PowerPoint media on natural appearance material in grade IV SD Negeri Pasi Pinang, Meureubo District, West Aceh. The research approach used is qualitative research with the type of research used is a classroom action research research subject totaling 12 grade IV students with 6 male students and 6 female students. Before the researcher took action, the observation results obtained in the pre-cycle got an average of 38.29%. After the researcher conducted the research and obtained the data, then the researcher processed the observation data on the interest in learning and the questionnaire on the student's interest in learning in the first cycle based on the results of the observation that the average percentage was 54.16% while the questionnaire results obtained a score of 2.06 and in the second cycle the observation results obtained an average of 88.75%, the results of the questionnaire obtained a score of 3.30. When the learning process takes place using PowerPoint media, students' attention is very big in learning when the teacher explains material about natural appearances. This shows that with the PowerPoint media the students' interest in learning has increased more than before in the material appearance of the fourth grade students of SD Negeri Pasi Pinang, Meureubo District, West Aceh.